Inter-Nesting Movements, Migratory Pathways, and Resident Foraging Areas of Green Sea Turtles (Chelonia mydas) Satellite-Tagged in Southwest Florida - Sloan, Kelly A.; Addison, David S.; Glinsky, Andrew T.; Benscoter, Allison M.; Hart, Kristen M. (Frontiers in Marine Science, 2022)
Globally, sea turtle research and conservation efforts are underway to identify important high-use areas where these imperiled individuals may be resident for weeks to months to years. In the southeastern Gulf of Mexico, recent telemetry studies highlighted post-nesting foraging sites for federally endangered green turtles (Chelonia mydas) around the Florida Keys. In order to delineate additional areas that may serve as inter-nesting, migratory, and foraging hotspots for reproductively active females nesting in peninsular southwest Florida, we satellite-tagged 14 green turtles that nested at two sites along the southeast Gulf of Mexico coastline between 2017 and 2019: Sanibel and Keewaydin Islands. Prior to this study, green turtles nesting in southwest Florida had not previously been tracked and their movements were unknown. We used switching state-space modeling to show that the Marquesas Keys, Florida Bay, and an area off Cape Sable (Everglades) are additional important foraging areas that support individuals that nest on southwest Florida mainland beaches. Turtles were tracked for 39 to 383 days, migrated for a mean of 4 days, and arrived at their respective foraging grounds between July and September. Turtles remained resident in their respective foraging sites until tags failed, typically after several months, where they established mean home ranges (50% kernel density estimate) of 296 km2. Centroid locations for turtles at common foraging sites were 1.1 to 36.5 km apart. The site off southwest Florida Everglades appears to be a high use area for these turtles during both inter-nesting and foraging; this location was also used by turtles that were previously satellite-tagged after nesting in the Dry Tortugas. Further evaluation of this important habitat is warranted. Understanding where and when imperiled yet recovering green turtles forage and remain resident is key information for designing surveys of foraging resources and developing additional protection strategies intended to enhance population recovery trajectories.